2022
DOI: 10.3389/fimmu.2022.1000626
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-to-lymphocyte ratio at 24h after thrombolysis is a prognostic marker in acute ischemic stroke patients

Abstract: BackgroundThe changes in the platelet-to-lymphocyte ratio (PLR) before and after recombinant tissue plasminogen activator (rtPA) treatment and the time point at which the PLR is a potentially valuable prognostic predictor in patients wit ischemic stroke remain largely unknown. Therefore, the purpose of this study was to explore the characteristics of the PLR and evaluate their effects on clinical outcomes before and 24 h after rtPA treatment.MethodsThis study included 741 consecutive patients with acute ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…In this study, we rstly reported that IL-10, IL-6, NLR,TNF-α, lymphocytes, PPR, LMR, PCT, neutrophils, cerebral herniation and NIHSS were associated with 30-day mortality in moderate and severe stroke patients, suggesting a multi-marker approach to improve outcome prediction in stroke patients, which consistent with previous research [ 26] [27][28][29] [30] . Most of these blood-based biomarkers are related to in ammation, suggesting that an elevated in ammatory state contribute to the mortality in moderate and severe stroke patients.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we rstly reported that IL-10, IL-6, NLR,TNF-α, lymphocytes, PPR, LMR, PCT, neutrophils, cerebral herniation and NIHSS were associated with 30-day mortality in moderate and severe stroke patients, suggesting a multi-marker approach to improve outcome prediction in stroke patients, which consistent with previous research [ 26] [27][28][29] [30] . Most of these blood-based biomarkers are related to in ammation, suggesting that an elevated in ammatory state contribute to the mortality in moderate and severe stroke patients.…”
Section: Discussionsupporting
confidence: 90%
“… 25 A recent study found that PLR at 24 hours after thrombolysis was a marker of 3-month functional outcome in AIS patients. 26 To our knowledge, our study is the first to report the association of PLR with functional outcomes at discharge in AIS patients, and the finding is similar to the 90-day functional outcomes of previous studies.…”
Section: Discussionsupporting
confidence: 87%
“…This may be because the PIV data in this study came from laboratory data at the time of admission. It has been confirmed that the predictive power of inflammation indicators 24 hours after thrombolytic therapy was stronger than that at admission [ 24 ]. Compared to SII, NLR and PLR, PIV includes not only lymphocyte and platelet, but also monocyte and neutrophil, suggesting that PIV is a more systemic indicator of inflammation.…”
Section: Discussionmentioning
confidence: 98%